Gonadotropin-Releasing Hormone Increased Pregnancy in Suckled Beef Cows Not Detected in Estrus and Subjected to a Split-Time Artificial Insemination Program - S. L. Hill; D. M. Grieger; K C Olson; J. R. Jaeger; K. R. Harmoney; C. R. Dahlen; M. R. Crosswhite; N. Negrin Pereira; S. R. Underdahl; B. W. Neville; J. Ahola; M. C. Fischer; et al. (Kansas Agricultural Experiment Station Research Reports, 2018)
Estrus-synchronization programs allow insemination of all females in a herd at one fixed time on the first day of the breeding season. Inseminating cows after they have expressed estrus increases pregnancy rate (PR) compared with cows that do not display estrus in a timed AI (TAI) program. Identification of estrus status can be facilitated by using estrus-detection patches. Varying AI timing according to estrus status has increased PR in some previous studies. Reducing the number of injections in a TAI program decreases labor requirements, stress on cows, and overall cost of the program. Previous studies have demonstrated that PR is not compromised in cows displaying estrus when the GnRH injection administered at AI is eliminated. A split-time AI program decreases the time between estrus expression and insemination compared with a single fixed-time AI when the first AI occurs before the recommended standard 60- to 66-h fixed time. Previous research has demonstrated that delaying AI results in approximately 50% more cows displaying estrus when compared with a single insemination time. Eliminating the GnRH injection at AI for cows displaying estrus in a split TAI program can reduce the number of GnRH injections required and the program cost. The objective of this study was to test the hypothesis that GnRH injection concurrent with split TAI program improves PR only in cows not displaying estrus.
Keywords: beef cattle; estrus detection; gonadotropin-releasing hormone; timed artificial insemination